(untitled) (Journal of Kidney Cancer, 2020)
Hereditary leiomyomatosis and renal cell cancer syndrome (HLRCC) associated renal cell carcinoma (RCC) is an aggressive form of type 2 papillary RCC caused by deficiency of the fumarate hydratase gene. For patients with metastatic disease, no standard treatment has been established with dismal prognosis. We report a case of metastatic HLRCC-associated RCC in a 65-year-old Japanese male whose clinical features mimicked advanced renal pelvic cancer. A durable response was achieved with a sequence of axitinib and nivolumab after cytoreductive and diagnostic nephrectomy. Their potential therapeutic roles in the management of metastatic HLRCC-associated RCC have been discussed based on its molecular and biological backgrounds.